Numerical Simulation of the Performance of a Twin Scroll Radial Turbine at Different Operating Conditions. (2nd June 2019) - Cravero, Carlo; De Domenico, Davide; Ottonello, Andrea
Abstract : Twin scroll radial turbines are increasingly used for turbocharging applications, to take advantage of the pulsating exhaust gases. In spite of its relevance in turbocharging techniques, scientific literature about CFD applied to twin scroll turbines is limited, especially in case of partial admission. In the present paper a CFD complete model of a twin scroll radial turbine is developed in order to give a contribution to literature in understanding the capabilities of current industrial CFD approaches applied to these difficult cases and to develop performance index that can be used for turbine design optimization purposes. The flow solution is obtained by means of ANSYS CFX ® in a wide range of operating conditions in full and partial admission cases. The total-to-static efficiency and the mass flow parameter (MFP) have been calculated and compared with the experimental database in order to validate the numerical model. The purpose of the developed procedure is also to generate a database for twin scroll turbines useful for future applications. A comparison between performances obtained in different admission conditions was performed. In particular the analysis focused on the characterization of the flow at volute outlet/rotor inlet section. A flow distortion index at rotor inlet was introduced to correlate the turbine performance and the flow nonuniformities generated by the volute. Finally the influence of the backside cavity on the performance parameters is also discussed. The introduction of these new nonuniformity indices is proposed for volute design and optimization procedures.